Generation Y on the labour market and the new forms of education - Anca Cristina Irimia (Rădulescu) (EURINT)
The article examines the labour market needs of Generation Y and the significance of alternative learning methods. It highlights the impact of non-formal and informal education in developing workplace skills and abilities. Through a survey of Generation Y employees in Romania, the study evaluates the importance of new learning contexts for personal development, well-being, and continuous learning motivation. The research focuses on qualitative data analysis to explore the alternative learning experiences and needs of Generation Y in the labour market. Additionally, the article emphasizes the positive role of European youth programs in helping young people acquire valuable skills for the workforce.